Prevalence and Factors Influencing Elderly Abuse: A Descriptive Study of Jureli Village, Bakaiya - Timalsina, Keshab Prasad (International Research Journal of MMC, 2021)
The elderly abuse in a family is one of the most challenging problems in a society. The present study aims to assess the prevalence of elderly abuse in the family environment of JureliTole of Bakaiya Rural Municipality. The study also presents various risk factors that influence the prevalence of Elderly abuse. A descriptive cross-sectional study was carried out among 103 elders taken from household survey by using census method. The data were collected through a face-to-face structured interview schedule. The descriptive and regression analysis of the collected data showed that the prevalence of elderly abuse was 46.6% in the study population. This study measured significant association (p<0.05) of overall abuse against the elder with only two socio-demographic variables (literacy status and health status) among the variables (gender, age groups, living with or without spouse, literacy status, health status, dependency status, and income level). The results showed that the elders with/without spouse had the highest odds ratio to be abused (2.19 times) followed by gender (1.64 times), and health status (1.25 times). Although this study found lower prevalence than many previous studies, it is still significant and needs to be prevented. Based on the study, it can be said that living without a spouse, with poor health, and being female are the major predictive descriptors for elderly abuse.The policies and programs are needed for the prevention of elderly abuse which may require collective action from social, health and justice sectors.